Subcycling Strategy for Finite‐Volume Updated‐Lagrangian Methods Applied to Fluid–Structure Interaction - Chantrait, Teddy; Chevaugeon, Nicolas; Del Pino, Stéphane; Gangloff, Alexandre; Labourasse, Emmanuel (International journal for numerical methods in engineering, 2025)
ABSTRACT In this article, we propose and investigate an explicit partitioned method for solving shock dynamics in fluid–structure interaction (FSI) problems. The method is fully conservative, ensuring the local conservation of mass, momentum, and energy, which is crucial for accurately capturing strong shock interactions. Using an updated‐Lagrangian finite‐volume approach, the method integrates a subcycling strategy to decouple time steps between the fluid and structure, significantly enhancing computational efficiency. Numerical experiments confirm the accuracy and stability of the method, demonstrating that it retains the key properties of monolithic solvers while reducing computational costs. Extensive validation across 1D and 3D FSI problems shows the method's capability for large‐scale, fast transient simulations, making it a promising solution for high‐performance applications.